Programmable budgetary funds as a public administration instrument: methodology for digital assurance of targeted use of public finances in Ukrainee - Basiuk , Oleksandr (Pressing Problems of Public Administration, 2025)
This article substantiates the concept of programmable budgetary funds as a public administration instrument that integrates the program-target budgeting method with digital technologies for verifying the targeted use of public finances. Programmable budgetary funds are conceptualized as an organizational-technological regime for managing budget appropriations, wherein budgetary commitments and payments are accompanied by machine-readable execution rules, digital proofs of compliance with established conditions, and continuous risk-oriented monitoring. This approach enables the transformation of normative requirements of budget legislation and budget program parameters into formalized verification algorithms executed at the payment decision stage, substantially reducing the dependence of fiscal discipline on post-factum control.A digital implementation methodology is proposed, encompassing the formalization of a digital budget program passport as a source of machine-readable rules, the establishment of a programmable budgetary commitments registry as a unified identifier of cash flows linked to expected outcomes, integration with treasury service systems, electronic procurement platforms, open data systems, and state registries through interoperability mechanisms, implementation of an evidence-based model for confirming compliance with conditions, and institutionalization of transparency and accountability through open data and public analytics. The boundaries of application and implementation risks are analyzed, particularly legal constraints, organizational barriers, and cybersecurity threats, alongside substantiation of the necessity to maintain principles of human oversight and explainability of algorithmic decisions within the context of budgetary control.